Wireless sensors system for broken rotor bar fault monitoring using wavelet analysis - Mehrjou, Mohammad Rezazadeh; Mariun, Norman; Karami, Mahdi; Misron, Norhisam; Mohd Radzi, Mohd Amran (IOP Publishing, 2015)
Accurate condition monitoring prevents unexpected failures in electrical systems including induction machines, and hence improves their performance significantly. To enhance the reliability of condition monitoring systems, wireless sensor systems are developed. In the recent years, researchers have placed considerable emphasis on developing cost-effective scheme using wireless sensor systems for fault diagnosis of equipments in industry. As broken rotor bar is one of the main causes of malfunction in electrical motors, this paper proposes a method for early detection of this failure in induction machines using wireless sensor system. In this respect, a test bed is developed where a sensor measures the motor current and then a microcontroller connected to this current sensor read and send the data to wireless sensor for remote real time data analysis. In the receiver unit, a Lab VIEW based program is developed to store data in a database and MATLAB is used for signal processing and fault.